2019
DOI: 10.12691/education-7-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Problem Solving Capabilities among Students Given a Problem-Based Learning Blended Learning with Conventional Learning

Abstract: There are five mathematical skills that students must have in one of them is problem-solving. The implementation of problem-based blended learning is expected to demonstrate differences in problem-solving skills that are given problem-based learning blended learning and students who are given conventional learning. It is also known that there are interactions between the initial mathematical ability (KAM) and the learning model of problem-solving capabilities so that this is the purpose of this research. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…This interactive and collaborative learning environment likely fosters enhanced comprehension, thereby positively influencing the mean ability scores. This finding aligns with previous research by Siregar et al (2019), who similarly observed that students' mathematical problem-solving abilities were superior when taught through blended learning compared to conventional methods. However, it contrasts with the findings of Adesoji (2008), who reported no significant differences in ability groupings.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…This interactive and collaborative learning environment likely fosters enhanced comprehension, thereby positively influencing the mean ability scores. This finding aligns with previous research by Siregar et al (2019), who similarly observed that students' mathematical problem-solving abilities were superior when taught through blended learning compared to conventional methods. However, it contrasts with the findings of Adesoji (2008), who reported no significant differences in ability groupings.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Dengan demikian dapat disimpulkan bahwa blended learning adalah pembelajaran yang menggabungkan instruksi langsung (offline) dan tidak langsung (online) atau mengombinasikan pembelajaran tatap muka yang didukung oleh TIK. Model pembelajaran blended learning "There are differences in problem-solving skills of students who are given learning-based blended learning problems with students who are given conventional learning" [17]. Selain itu dengan penerapan model pembelajaran blended learning dapat meningkatkan hasil belajar dan motivasi belajar siswa [18].…”
Section: Pendahuluanunclassified
“…Pengaruh metode konvensional seperti ceramah akan sangat terasa seperti menurunnya konsetrasi siswa, minat dan motivasi siswa berkurang terhadap gurunya ataupun mata pelajarannya, serta meningkatnya ketidakaktifan siswa ketika proses pembelajaran berlangsung. Peranan guru yang dominan dan hanya sebagai objek kontrol dalam pembelajaran konvensional membuat pembelajaran sejarah kurang berkesan (Siregar et al, 2019).…”
Section: Seminar Nasional Pembelajaran Sejarah (Snps Uns 2020)unclassified